2012
DOI: 10.1074/jbc.m112.373746
|View full text |Cite
|
Sign up to set email alerts
|

The Endoplasmic Reticulum Stress Transducer BBF2H7 Suppresses Apoptosis by Activating the ATF5-MCL1 Pathway in Growth Plate Cartilage

Abstract: Background:The endoplasmic reticulum stress transducer BBF2H7 is expressed in proliferating chondrocytes. Results: Apoptosis is promoted in the cartilage of Bbf2h7 Ϫ/Ϫ mice. BBF2H7 activates Atf5 transcription, followed by apoptosis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 46 publications
3
29
0
Order By: Relevance
“…Chondrocytes express the ATF6 homolog, BBF2H7, which may prevent CHOP-mediated apoptotic signaling [72]. In models of MCDS, UPR activation in hypertrophic chondrocytes results in the dedifferentiation of chondrocytes to a prehypertrophic state [48,107].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chondrocytes express the ATF6 homolog, BBF2H7, which may prevent CHOP-mediated apoptotic signaling [72]. In models of MCDS, UPR activation in hypertrophic chondrocytes results in the dedifferentiation of chondrocytes to a prehypertrophic state [48,107].…”
Section: Discussionmentioning
confidence: 99%
“…In BBF2H7 −/− mice, chondrocyte proliferation is severely perturbed (Table 2), and this is likely to be due to the insufficient secretion of ECM proteins required for chondrocyte maturation in the growth plate [60]. Interestingly, BBF2H7 also appears to have a key role in preventing UPR-induced apoptosis in chondrocytes [72]. This could explain earlier findings in metaphyseal chondrodysplasia, Schmid type (MCDS) chondrocytes, which do not undergo apoptosis despite elevated CHOP expression [48,73].…”
Section: The Unfolded Protein Response Has An Essential Role In Chmentioning
confidence: 99%
“…Newman and Keating also reported that ATF5 acted as a C/EBPcbinding transcription factor in comprehensive protein array analysis [30]. ATF5 is a stress response transcription factor whose expression is regulated by posttranscriptional regulation [31], translational regulation [32,33] and post-translational regulation [34][35][36][37][38][39][40] in response to cellular stresses including endoplasmic reticulum (ER) stress [33,41], arsenite exposure [32,33,36] and amino acid limitation [31,32]. Limitation of a single amino acid (glutamine, methionine or leucine) in the cell culture medium increased ATF5 mRNA levels in HeLaS3 cells [31].…”
Section: Introductionmentioning
confidence: 99%
“…Related to this finding, but somewhat perplexing is the observation that chemical inhibition of LonP1 protease activity using CDDO activates the UPR mt , as well as increasing ATF4 mediated gene induction (75), indicating a possible bidirectional regulatory linkage between ATF4 and LonP1. Another finding that could serve as a molecular integration point between the UPR ER and UPR mt was shown in chondrocytes, where the ATF6 family member, BBF2H7, induces typical UPR ER genes, as well as the regulator of the UPR mt , ATF5 (76). In an examination of the effects of drugs that dysregulate mitochondrial proteostasis in HeLa, 293T, and COS7 cells, as well as maneuvers that cause mitochondrial proteostatic stress, in vivo, it was shown that via activation of the ISR, ATF4 but not ATF5 responds to dysregulated mitochondrial proteostasis and activates the expression of cytoprotective genes (77).…”
Section: Integrating Er and Mitochondrial Proteostasismentioning
confidence: 98%